Peranan Kepala Desa Muara sungai dalam Pengelolaan Pasar - Yelli Aswariningsih (COSTING : Journal of Economic, Business and Accounting, 2019)
Village planning provides the flexibility and opportunity for villages to explore local initiatives (ideas, desires and local will) which are then institutionalized into policies, programs and activities in the field of village governance and development. The purpose of the study was to explain the role of the village head in the management of the Muara Sungai village market in the management of the village market in the Muara river village, CambaiPrabumulih Timur District. The research method is descriptive-analytical with the juridical-empirical method. The results showed that the role of Muara Sungai village head Cambai Subdistrict, Prabumulih Timur Regency in issuing a policy in village market management had not been done properly and correctly, this proved the village head could not issue a form of policy according to his authority, so that it did not provide benefits and income to the village treasury. This is seen as unproductive due to unclear management patterns. So in essence the village market has not provided benefits to increase village income. Therefore, the management of village markets should be improved through standardized management mechanisms and systems as well as accountability in order to avoid irregularities. Keywords : Management, Market, Village, Village Head